1988
DOI: 10.1002/jbmr.5650030408
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phenytoin on calcium uptake in osteoblastic cells

Abstract: The effects of phenytoin (diphenylhydantoin, DPH) on calcium uptake in osteoblastic cells were studied to elucidate the potential mechanism of action of this antiepileptic drug on bone metabolism. Preincubation of the human osteoblastic osteosarcomal cell line, SaOS-2, and normal rat osteoblastic cells with DPH decreased basal calcium uptake. This inhibition occurred at DPH doses from 0.1 to 50 micrograms/ml. Parathyroid hormone (PTH) and prostaglandin E2 (PGE2) increased calcium uptake in the SaOS-2 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…phenytoin and carbamazepin, on human osteoblast-like bone cells. Both drugs have been suspected to influence bone metabolism and BMD (Valimaki et al, 1994;Sheth et al, 1995;Hoikka et al, 1984;Dziak et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…phenytoin and carbamazepin, on human osteoblast-like bone cells. Both drugs have been suspected to influence bone metabolism and BMD (Valimaki et al, 1994;Sheth et al, 1995;Hoikka et al, 1984;Dziak et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…One of these is bone turnover, which reflects changes in the rate of bone remodeling, assessed by measurements of alterations in biochemical markers of bone resorption and formation. Animal studies have suggested that PHT causes bone loss due to elevated bone resorption (Takahashi et al, 2000; Onodera et al, 2001; Takahashi et al, 2004), but PHT may also affect bone‐forming osteoblasts directly via a biphasic mechanism, as low doses seem to stimulate and high therapeutic doses to inhibit osteoblast proliferation and differentiation (Dziak et al, 1988; Ohta et al, 1995; Lau et al, 1995; Ikedo et al, 1999; Feldkamp et al, 2000). For VPA there is evidence for decreased (Tsukahara et al, 2002), unaltered (Guo et al, 2001), or increased bone turnover (Rieger‐Wettengl et al, 2001; Sato et al, 2001; Oner et al, 2004).…”
mentioning
confidence: 99%
“…A possible mechanism may be the Bsm I VDR polymorphism affecting calcium metabolism, and/or osteoblast and osteoclast function. In previous studies, AEDs, especially CYP enzyme inducer, have been shown to induce bone loss via the alteration of osteoclast differentiation and function (Dziak et al., 1988; Koide et al., 2009). Vitamin D receptor polymorphism, when present, can alter bone metabolism and, therefore, affect the susceptibility to the osteopenic effects of AEDs.…”
Section: Discussionmentioning
confidence: 99%